Melatonin and its metabolite N(1)‐acetyl‐N(1)‐formyl‐5‐methoxykynuramine improve learning and memory impairment related to Alzheimer's disease in rats. Issue 2 (13th December 2019) - Rong, Kai; Zheng, Hong; Yang, Ruibo; Liu, Xiaoli; Li, Liya; Chen, Ning; Zhao, Gang; Gong, Chengxin; Deng, Yanqiu
Abstract: The aim of this study was to investigate the effect of melatonin (MT) and its metabolite N (1)‐acetyl‐ N (2)‐formyl‐5‐methoxykynuramine (AFMK) on Alzheimer‐like learning and memory impairment in rats intracerebroventricularly injected with streptozotocin (STZ). The results showed that the escape latency of the STZ group was longer than that of the control (CON), MT, and AFMK groups. Increased levels of hyperphosphorylated tau, neurofilament proteins, and malondialdehyde and decreased superoxide dismutase levels were observed in the brains of the rats from the STZ group compared with the brains of the rats from the CON, MT, AFMK high and low group. These results suggest that exogenous MT and AFMK can improve memory impairment and downregulate AD‐like hyperphosphorylation induced by STZ, most likely through their antioxidation function. Meanwhile, we found that an equal dose of AFMK had a stronger effect than that of MT. Our results indicate that MT and its metabolite AFMK represent novel treatment strategies for Alzheimer's disease.